Native American History as Counter-Discourse in James Welch’s Narratives: The Examples of “Fools Crow” and “Killing Custer”. - Garuba, Issa Omotosho (English Studies at NBU, 2024)
A peculiar dimension in the Native American writing is the documentation of the history of the Native Americans’ traditional lives before, during and after their encounter with the white settlers. It is a development that is essentially explicable within the purview of postcolonial discourse, given that, in some contexts, historical distortions from the perspective of the ‘other’ have been asserted as the rationale for such creative explorations on the part of the Native writers. In the context of this study, such a dimension, with particular reference to James Welch’s novels, is considered as, indeed, counter-discursive. Two of his novels, Fools Crow and Killing Custer, are selected with a view to assessing how the historical documentations in the texts translate to counter-discourses in the context of the Native Americans’ historical evolution. The study reveals that, while the Native American histories in the texts dovetail into each other, they are largely inspired by the Native Americans’ colonial experience vis-à-vis the need to represent their history from the perspective of ‘us’ as opposed to ‘other’. It concludes that the narratives have, in a significant way, performed the allegorical configuration function, as a counter-discourse strategy described by Slemon (1987). This holds in that they have conceivably assumed ‘readings’ and ‘contestations’ of the previously textualised colonial experience of the Native Americans from the perspective of the ‘other’.